Are people at high risk for diabetes visiting health facility for confirmation of diagnosis? A population-based study from rural India. Issue 1 (1st January 2018) - Srinivasapura Venkateshmurthy, Nikhil; Soundappan, Kathirvel; Gummidi, Balaji; Bhaskara Rao, Malipeddi; Tandon, Nikhil; Reddy, K. Srinath; Prabhakaran, Dorairaj; Mohan, Sailesh
ABSTRACT: Background : India is witnessing a rising burden of type 2 diabetes mellitus. India's National Programme for Prevention and Control of Diabetes, Cancer, Cardiovascular diseases and Stroke recommends population-based screening and referral to primary health centre for diagnosis confirmation and treatment initiation. However, little is known about uptake of confirmatory tests among screen positives. Objective : To estimate the uptake of confirmatory tests and identify the reasons for not undergoing confirmation by those at high risk for developing diabetes. Methods : We analysed data collected under project UDAY, a comprehensive diabetes and hypertension prevention and management programme, being implemented in rural Andhra Pradesh, India. Under UDAY, population-based screening for diabetes was carried out by project health workers using a diabetes risk score and capillary blood glucose test. Participants at high risk for diabetes were asked to undergo confirmatory tests. On follow-up visit, health workers assessed if the participant had undergone confirmation and ask for reasons if not so. Results : Of the 35, 475 eligible adults screened between April 2015 and August 2016, 10, 960 (31%) were determined to be at high risk. Among those at high risk, 9670 (88%) were followed up, and of those, only 616 (6%) underwent confirmation. Of those who underwent confirmation, 'lack of symptoms of diabetes warranting visit to health facility' (52%) and 'being at high risk was not necessary enough to visit' (41%) were the most commonly reported reasons for non-confirmation. Inconvenient facility time (4.4%), no nearby facility (3.2%), un-affordability (2.2%) and long waiting time (1.6%) were the common health system-related factors that affected the uptake of the confirmatory test. Conclusion : Confirmation of diabetes was abysmally low in the study population. Low uptake of the confirmatory test might be due to low 'risk perception'. The uptake can be increased by improving the population risk perception through individual and/or community-focused risk communication interventions.